Suprascapular Nerve Entrapment Caused by Protrusion of an Intraosseous Ganglion of the Glenoid into the Spinoglenoid Notch: A Rare Cause of Posterior Shoulder Pain - Daichi Ishimaru; Akihito Nagano; Nobuo Terabayashi; Yutaka Nishimoto; Haruhiko Akiyama (Case Reports in Orthopedics)
We describe a case of suprascapular nerve entrapment caused by protrusion of an intraosseous ganglion of the glenoid into the spinoglenoid notch. A 47-year-old man with left shoulder pain developed an intraosseous cyst in the left glenoid, which came into contact with the suprascapular nerve. The area at which the patient experienced spontaneous shoulder pain was innervated by the suprascapular nerve, and 1% xylocaine injection into the spinoglenoid notch under ultrasonographic guidance relieved the pain. Therefore, we concluded that the protrusion of an intraosseous cyst of the glenoid into the spinoglenoid notch was a cause of the pain, and performed curettage. Consequently, the shoulder pain was resolved promptly without suprascapular nerve complications, and the cyst was histologically diagnosed as an intraosseous ganglion. This case demonstrated that the intraosseous ganglion of the glenoid was a benign lesion but could be a cause of suprascapular nerve entrapment syndrome. Curettage is a useful treatment option for a ganglion inside bone and very close to the suprascapular nerve.